Application of Sephadex LH-20 for Microdetermination of Dopamine by Solid Phase Spectrophotometry. (28th November 2012) - Taghdiri, Mehdi; Mohamadipour-taziyan, Arash
Abstract : A sensitive spectrophotometric method for the determination of dopamine was carried out without any separation steps. Bromocresol green is adsorbed on Sephadex LH-20 gel but the sorption decreases in the presence of dopamine due to ion-pair formation between bromocresol green and dopamine in solution. This attenuation was used to the microdetermination of dopamine by measurement of absorbance of the solid phase (Sephadex LH-20 gel) in a 1.0 mm cell at 625 nm. Dopamine could be determined in the concentration range of 0.4–1.6  μ g mL −1 (10-mL Sample volume) with a relative standard deviation (RSD) of 0.03% (n = 4 ). The detection limit was obtained, 0.26  μ g mL −1 (1.7  μ M). The method was used for determination of dopamine in pharmaceutical injection sample and satisfactory result was obtained.